Adsorption of Methylene Blue on Prepared Charcoal from Molasses Waste (Journal of Engineering, 2019)
Recently, important efforts have been made in an attempt to search for the cheapest and ecofriendly alternatives adsorbents. In the present work, waste molasses from Iraqi date palm (Zahdi) had been used as a provenance to produce charcoal for the removal of methylene blue (MB) dye from water. The optimum prepared charcoal was obtained at 150 C, by increasing temperature to 175 C, the charcoal had almost converted to ash. The obtained charcoal have been inspected for properties using scanning electron microscope (SEM), atomic force microscope (AFM), porosity and surface area. Adsorption data were optimized to Langmuir and Freundlich and adsorption parameters have been evaluated. The thermodynamic parameters like a change in Gipps energy (ΔG), enthalpy (ΔH) and entropy (ΔS). The effects of increasing temperature on adsorption capacity were investigated and the results indicate that pseudo-second-order kinetics model could be presented the adsorption dynamic data. The resultant values for the heat of adsorption and the free energy indicated that adsorption of methylene blue dye is preferred at low temperatures.